Functional spectrum of USP7 pathogenic variants in Hao–Fountain syndrome: Insights into the enzyme’s activity, stability, and allosteric modulation - Emilie J. Korchak; Mona Sharafi; Isabella Jaen Maisonet; Andres Salazar-Chaparro; Irina V. Semenova; Hamza Khan; Alison L. O’Neil; Pilar Caro; Christian P. Schaaf; Sara J. Buhrlage; Irina Bezsonova (Proceedings of the National Academy of Sciences, 2025)
Hao–Fountain syndrome is a rare neurodevelopmental disorder caused by mutations in the deubiquitinating enzyme Ubiquitin-Specific Protease 7 (USP7). Due to the novelty of the disease and its poorly understood molecular mechanisms, treatments for the syndrome are currently lacking. This study examines the effects of 11 patient-derived variants located within the catalytic domain of USP7, focusing on their impact on the enzyme’s activity, thermodynamic stability, and substrate recognition. Our findings reveal a spectrum of functional consequences, ranging from complete inactivation to hyperactivation of USP7. Notably, we identify a specific subset of pathogenic variants whose catalytic activity can be significantly boosted using an allosteric activator, MS-8. These results provide insight into USP7 malfunction in Hao–Fountain syndrome–linked variants and pave the way for improved prognostic approaches and targeted treatments in the future.